Newly formed and remodeled human bone exhibits differences in the mineralization process. (1st March 2020) - Roschger, Andreas; Wagermaier, Wolfgang; Gamsjaeger, Sonja; Hassler, Norbert; Schmidt, Ingo; Blouin, Stéphane; Berzlanovich, Andrea; Gruber, Gerlinde M.; Weinkamer, Richard; Roschger, Paul; Paschalis, Eleftherios P.; Klaushofer, Klaus; et al.
Abstract: During human skeletal growth, bone is formed via different processes. Two of them are: new bone formation by depositing bone at the periosteal (outer) surface and bone remodeling corresponding to a local renewal of tissue. Since in remodeling formation is preceded by resorption, we hypothesize that modeling and remodeling could require radically different transport paths for ionic precursors of mineralization. While remodeling may recycle locally resorbed mineral, modeling implies the transport over large distances to the site of bone apposition. Therefore, we searched for potential differences of size, arrangement and chemical composition of mineral particles just below surfaces of modeling and remodeling sites in femur midshaft cross-sections from healthy children. These bone sites were mapped using scanning synchrotron X-ray scattering, Raman microspectroscopy, energy dispersive X-ray analysis and quantitative backscattered electron microscopy. The results show clear differences in mineral particle size and composition between the sites, which cannot be explained by a change in the rate of mineral apposition or accumulation. At periosteal modeling sites, mineral crystals are distinctly larger, display higher crystallinity and exhibit a lower calcium to phosphorus ratio and elevated Na and Mg content. The latter may originate from Mg used for phase stabilization of mineral precursors and therefore indicate different time periods for mineral transport. We conclude that the mineralization process is distinctively different between modeling and remodeling sites due to varying requirements for the transport distance and, therefore, the stability of non-crystalline ionic precursors, resulting in distinct compositions of the deposited mineral phase. Statement of Significance: In growing children new bone is formed either due to apposition of bone tissue e.g. at the outer ridge of long bones to allow growth in thickness (bone modeling), or in cavities inside the mineralized matrix when replacing tissue (bone remodeling). We demonstrate that mineral crystal shape and composition are not the same between these two sites, which is indicative of differences in mineralization precursors. We suggest that this may be due to a longer mineral transport distance to sites of new bone formation as compared to remodeling where mineral can be locally recycled. Graphical abstract: Image, graphical abstract